2013
DOI: 10.1016/j.regsciurbeco.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Small homes, public schools, and property tax capitalization

Abstract: The research program of the Center for Economic Studies (CES) produces a wide range of economic analyses to improve the statistical programs of the U.S. Census Bureau. Many of these analyses take the form of CES research papers. The papers have not undergone the review accorded Census Bureau publications and no endorsement should be inferred. Any opinions and conclusions expressed herein are those of the author(s) and do not necessarily represent the views of the U.S. Census Bureau. All results have been revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Evidence that the capitalization of school quality occurs on a per lot basis rather than on a per square foot of land basis is provided. Similarly, Gallagher, Kurban and Persky (2013) examine the small home property tax relation to adjust for unobservable amenities associated with school quality that may be related to house size. They find that local property taxes are nearly fully capitalized into the price of small homes.…”
Section: Literature Review and Motivationmentioning
confidence: 99%
“…Evidence that the capitalization of school quality occurs on a per lot basis rather than on a per square foot of land basis is provided. Similarly, Gallagher, Kurban and Persky (2013) examine the small home property tax relation to adjust for unobservable amenities associated with school quality that may be related to house size. They find that local property taxes are nearly fully capitalized into the price of small homes.…”
Section: Literature Review and Motivationmentioning
confidence: 99%
“…If this is true then comparing the sales prices of similar homes close to the municipal border, but on opposite sides, allows an unbiased estimate of property tax capitalization. Gallagher et al (2013) applied the border discontinuity method to school-district boundaries in Cook County, IL (excluding Chicago). The design of the study goes further than applying the border method to all district boundaries, instead using only boundaries within a city that divides by school district.…”
Section: Property Taxes and Incentivesmentioning
confidence: 99%
“…In addition to applying the border method at specific boundaries, the authors highlighted that public services can be better controlled for using the sale of small homes, as these homes are less likely to be occupied by families with children and thus the buyers will not be interested in school quality. After taking all these precautions to isolate the effect of school district property taxes, Gallagher et al (2013) found that these taxes are nearly fully capitalized into home values (97%).…”
Section: Property Taxes and Incentivesmentioning
confidence: 99%
“…For example, the elderly may migrate away from communities with high school district taxes (Farnham and Sevak 2006; Shan 2010) and, therefore, these values may partially reflect patterns of fiscal mobility. A similar logic applies to the variable, v s t r , as communities’ housing values may be lower where property taxes are highest (Palomon and Smith 1998; Gallagher, Kurban, and Persky 2013).…”
Section: The Impact Of Elderly Households On Per-student Education Rementioning
confidence: 99%
“…These new units of observation are referred to as pseudo-unified districts, reflecting their similarity to true unified districts in that they represent students enrolled at both the elementary and secondary level. See Kurban, Gallagher, and Persky (2012) and Gallagher, Kurban, and Persky (2013) for similar applications of pseudo-unified school districts.…”
mentioning
confidence: 99%